Dynamic hyperinflation and pulmonary inflammation: a potentially relevant relationship? - A. Agusti; J. B. Soriano (European Respiratory Review, 2006)
In patients with moderate-to-severe chronic obstructive pulmonary disease (COPD), end-expiratory lung volume increases under conditions of greater minute ventilation (e.g. exercise). This abnormal response is termed dynamic hyperinflation (DH) and has now been recognised as a key determinant of symptomatology and exercise intolerance in COPD. Reduced elastic recoil, loss of alveolar attachments and increased airway resistance are the mechanical factors traditionally invoked to explain the occurrence of DH in COPD. An abnormal inflammatory response to, most frequently, tobacco smoking is a key pathophysiological component of COPD, but its potential relationship with DH has not been directly investigated and is poorly understood. The present article discusses, first, the mechanisms by which DH can enhance inflammation in COPD (including cellular stretching, tissue damage and danger signals, hyperventilation and hypoxia). It then reviews how the abnormal inflammatory response that characterises the disease can augment DH (oedema and increased airway resistance, increased mucus production and alveolar destruction). Finally, it speculates that if these relationships eventually prove to be real, then the use of long-acting bronchodilators may help reduce the inflammatory load of these patients and, conversely, the use of anti-inflammatory therapy can contribute to the reduction of DH.